Environmental impact assessment of SONARA's oil sludge landfill in BATOKE, south-west Cameroon - Mefomdjo Fotie Blanche; Elhadji Daou Ibrahim; Boukari Harouna; Kapta Momegni Christian; Raihanatou Amadou; Tchuikoua Louis Bernard; Mambou Ngueyep Luc Leroy (Heliyon)
The focus of this study was to assess the environmental impact of the BATOKE oil sludge dump. A field visit was conducted to evaluate the condition of the site, followed by the sampling of oil sludge, BATOKE river water, soil, and locally grown manioc and macabo tubers. Subsequent physico-chemical characterization revealed parameters such as pH, electrical conductivity, total hydrocarbons, COD, BOD5, TSS, major cations and anions, as well as heavy metals including iron, copper, zinc, nickel, chromium, lead, cadmium, mercury, arsenic, calcium, potassium, titanium, zirconium, and rubidium. The environmental impact was assessed using the Contamination Index calculation and the Correlation Matrix. Results indicated that most physical parameters met standards, except for the electrical conductivity of water and soil. However, elevated levels of iron, chromium, lead, cadmium, mercury, arsenic, and ammonium ion were found in the BATOKE River water. The soil showed heavy contamination with various metals, and cassava and macabo tubers were also found to be contaminated. The contamination index calculations confirmed severe pollution in the BATOKE environment, with a risk of further escalation without remediation efforts.